EFFECT OF CRM PERCEPTION AND SERVICE QUALITY SATISFACTION ON CUSTOMER LOYALTY IN BANKING SECTOR (IITM Journal of Business Studies, 2025)
This paper addresses the critical imperative for  banking institutions, particularly in India, to  cultivate enduring relationships with customers  with a focus on Customer Relationship  Management (CRM) and its effect on service  quality satisfaction and customer loyalty. The  research employs Partial Least Square Structural  Equation Modeling (PLS-SEM) to analyze the  relationship between CRM perception and  customer loyalty with customer satisfaction  from service quality acting as a mediator.  The findings reveal significant positive path  coefficients, affirming that a positive perception  of CRM practices influences customer  satisfaction from service quality as well as  customer loyalty. Additionally, the research  establishes a significant and positive impact of  customer satisfaction on customer loyalty, and  identifies a complementary partial mediation  effect suggesting that customer satisfaction  from service quality mediates between CRM  perception and customer loyalty relationship.  These findings provide a robust framework  for understanding the dynamics shaping  customer-bank relationship, allowing banking  firms to strategically enhance customer  satisfaction and loyalty. The study emphasizes  the ongoing need for banks to adapt and refine  their CRM practices to align with the evolving  needs of customers, ultimately adding value  to all stakeholders involved in the financial  landscape.
Keywords: Customer Relationship Management; Customer Relationship Management Perception; Customer Satisfaction; Customer Loyalty; Banking